2nd International Congress of Asia Oceania Neurotrauma Society Tokyo, Jepun 06-07 Mac 2010 - Zamzuri l, ldris (Pusat Pengajian Sains Perubatan, 2010)
Multimodakity monitoring of severb' head injured patientsMalaysia eixperiense